Un flâneur al pascolo. Gianni Celati e l’esperienza dell’ambiente - Brysiak , Anna Małgorzata (Studia Romanica Posnaniensia, 2022)
The essay aims to analyze the writings of Gianni Celati and his way of ‘re-narrating’ and ‘re-mapping’ the environment in contemporary times, focusing on two trilogies, namely Narratori delle pianure (1985), Quattro novelle sulle apparenze (1987) and Verso la foce (1989), as well as on the collections of short stories Un eroe moderno (2008), Il benessere arriva in casa Pucci (2008), and Selve d’amore (2013). The paper discusses how the themes addressed by the author, who assumes the role of a flâneur of postmod- ernism, are a way to express his continuous nostalgia for the naturalness, simplicity, and originality of living and narrating.